Role of Program Curriculum in Building Social Skills and Sports Coaching in Academic and Career Development Under Sports Humanities and Sociology - Jiang, Zhenglu; Yin, Jiesen (Frontiers in Psychology, 2022)
The role of program curriculum in building social skills and sports coaching in academic and career development under sports humanities and sociology has been examined in the present study. Social skills coaching and sports coaching for the students are two important factors that need to be considered by the universities around the globe in order to improve the organizational climate which ultimately leads toward better career and academic development of the students. To examine this, the present study took data from 308 members of sports federation enrolled in different programs in the universities in China through the use of questionnaire. Data was analyzed with the help of structural equation modeling (SEM) technique using Smart PLS. The study found a significant relationship of social skills with academic development and organizational climate, a significant relationship of sports coaching on organizational climate and career development, a significant relationship between organizational climate and career development. Also, organizational climate acts as a partial mediator between sports coaching and career development. However, the study revealed that organizational had insignificant relationship with academic development, and organizational climate did not mediate between social skills coaching and academic development among students. While hiring the sports personnel universities must consider the competency of the coach using effective methods like physical test, pre-assessments, psychological tests etc. Second, the universities in China have to develop a culture of social skills and sports in order to improve academic and career development.